Exploring Entrepreneurial Action in a Small Firm using Identity Theory - Fox, Gregory (2009)
There is a great deal of potential for ethnography to play a far more significant role in organisation and management studies. Under this premise, this research looks to understand the nuances and to provide insights into how things work in a small electrical systems integration business using ethnographic methods. Borrowing heavily from identity theory, this dissertation investigates the practical elements of entrepreneuring and its implications for entrepreneurial identity using participant observation and interviews to extract salient results. The work begins with a brief overview of the methodological considerations for ethnography before moving to an examination of the theoretical principles behind research. The results of this research are then categorised thematically under individuality, psychology and relationships before concluding with an assessment of the relative success of this project.